DISTRIBUSI FREKUENSI CARCINOMA KOLOREKTAL DI BAGIAN BEDAH RUMAH SAKIT ISLAM SITI RAHMAH PADANG PERIODE 2017-2018 - Khomeini (Nusantara Hasana Journal, 2022)
Colorectal cancer often occurs in old age, more than 90% of this disease afflicts patients over the age of 40 years, with a peak incidence at the age of 60-70 years (elderly). This can happen because it is associated with mutations in the DNA of cells that make up the colonic wall that accumulates with age, as well as a decrease in the body's immune system which increases with age, which is characterized by a decrease in immunoglobulin production, lymphocyte configuration and its reaction against infection is reduced and decreased. the ability of the body's immune system to recognize foreign objects that enter the body. Colorectal cancer is found under the age of 40 years in people who have a history of ulcerative colitis or familial polyposis. Purpose of the study to determine the frequency distribution of colorectal carcinoma in the surgical section of Siti Rahmah Islamic Hospital, Padang for the 2017-2018 period. The sampling method used total sampling technique. Total sampling is a sampling technique where the number of samples is the same as the population. The population size obtained from the medical record data of the Siti Rahmah Padang Hospital in 2017-2018. The results showed that the most cases of prostate adenocarcinoma were high grade Gleason score (Gleason score 8-10), namely 43 (76.79%) cases and high expression AR 29 (51.80%) cases. Prostate adenocarcinoma with high grade Gleason score found more AR high expression than low AR expression. Statistically there is a significant relationship between high expression of AR and Gleason score (p=0.018). High expression of AR is an important marker for tumor progression. AR expression should be examined in cases of prostate adenocarcinoma to determine the patient's prognosis.